Pengembangan Platform LMS Asli Cerdas dalam Upaya Meningkatkan Literasi Digital Anak Usia Sekolah di Kota Samarinda sebagai Mitra Ibu Kota Nusantara (IKN): Innovation of the Asli Cerdas LMS Platform in Enhancing Digital Literacy Among School-Age Children in Samarinda - Sa'ad, Muhammad Ibnu; Nursobah; Pajar Pahrudin; Pitrasacha Adytia; Hanifah Ekawati; Salmon (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2025)
Digital literacy is a fundamental competency in preparing the younger generation to face the challenges of the digital transformation era. Samarinda City, as a strategic partner of the National Capital (IKN), plays an important role in preparing adaptive and tech-literate human resources. This study aims to develop a Learning Management System (LMS) platform called Asli Cerdas to enhance digital literacy among elementary and middle school students. The method used is descriptive-exploratory, involving 675 respondents from 10 districts in Samarinda. Instruments such as digital literacy questionnaires and field observations were used to collect both quantitative and qualitative data. The results showed that students had an average digital literacy index of 3.60, with the lowest score in the aspect of digital safety. Teachers showed better scores but still require technical training to maximize technology use. The Asli Cerdas platform was developed with features including local content, self-assessment tools, and offline access. Pilot testing of the platform showed a 24% improvement in students' understanding of digital literacy. This study recommends the adoption of locally based LMS platforms supported by regional policies to strengthen the digital learning ecosystem in areas that serve as partners to IKN